Propuesta de un plan para la gestión de residuos sólidos dentro del parque el Chapuzón, Bayamo-Cuba - Cepeda Hurtado, Marilin Tatiana (2013)
The research was conducted from October 2012 to January 2013, in the “Parque Río Bayamo” which is located in the city with the same name. In addition, it is the capital of the municipality Bayamo and it belongs to Granma Province. The principal objective consisted in proposing a plan that contributes to the integrated management of municipal solid waste, and according to this; it permits the management of solid waste in the park. In order to give effect to this purpose, the object of study was characterized by applying different techniques such as: the scientific observation and interviews. They were applied to obtain relevant information on the situation of solid waste and its management. The main causes were identified; they affect the management of municipal solid waste negatively (MSW). This information was taken as reference for the development of the integrated plan for the management of waste. The plan is considered as an important tool for the significant application of taxes which pay the environmental maintenance of the park, so raising the quality of life of employees and visitors. The evolution of society, driven by the development of productive forces; was assumed by different human groups. In fact, it was in agreement to their condition of having or not the means of production. This fact determines their ways of behavior, their values, their ways of social organization, their conception of the world; as well as their culture and the impact on nature and the environment….